METODE PEMBELAJARAN ESTAFET BERPUTAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM: PENGARUH TERHADAP HASIL BELAJAR SISWA KELAS VIII - Nadilah Nadilah; Leny Marlina; Rika Hasmayanti Agustina (Prodi Tadris Ilmu Pengetahuan Sosial FITK UIN Sumatera Utara Medan, 2026)
Students’ learning outcomes in Islamic Religious Education are often influenced by the learning methods used in the classroom. Learning activities that are still teacher-centered may reduce students’ participation and understanding of the material. Therefore, this study aimed to examine the effect of the Rotating Relay learning method on the learning outcomes of eighth-grade students in Islamic Religious Education. This study employed a quantitative approach using a one-group pretest-posttest design. The participants consisted of 36 eighth-grade students. Data were collected through tests, observation, and documentation, while hypothesis testing was conducted using the Wilcoxon Signed Rank Test because the data were not normally distributed. The findings showed that the mean pretest score of 52.22 increased to 84.17 on the posttest. The Wilcoxon Signed Rank Test produced an Asymp. Sig. (2-tailed) value of < 0.001, which is lower than 0.05. These results indicate a statistically significant difference between students’ learning outcomes before and after the implementation of the Rotating Relay learning method. Thus, the application of the Rotating Relay learning method was associated with improved learning outcomes in Islamic Religious Education among eighth-grade students.